Multi-wavelength Brillouin Raman Erbium Fiber Laser utilizing Captured Residual Raman Pump Power - Ismail A.; Helmi H.M.; Jamaludin M.Z.; Ker P.J.; Abdullah F.; Sulaiman A.H.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Erbium; Fiber lasers; Fibers; Brillouin fiber laser; Brillouin Stokes; Erbium doped fiber laser; Erbium doped fibers; Erbium fiber lasers; Lasing modes; Multi-wavelengths; Raman pump; Pumping (laser)